Pembelajaran IPA Berbasis Higher Order Thinking Skills di SD Era Society 5.0 - Dilah, Salsa (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2023)
ABTRACT In doing equity, the government program launched the era of society 5.0. The launch of the era of society 5.0 is an opportunity and challenge for the community, especially students, in improving learning skills as capital for the future. The need for students to face the challenges of the era of society 5.0, then students must apply HOTS (higher order thinking skills) based learning, which is a student's thinking process with higher cognitive levels developed from various learning taxonomy concepts. The purpose of students applying HOTS is to improve students' ability to think critically at a higher level. This type of research is qualitative research with literature study method. The result of this research is that applying HOTS-based learning in high grade elementary schools trains students' ability to think critically, creatively, solve their own problems with their own knowledge. Keywords: HOTS, IPA, Era Society 5.0 ABSTRAK Dalam melakukan pemerataan, program pemerintah mencanangkan era society 5.0. Diluncurkannya era society 5.0 ini jadi peluang dan tantangan untuk masyarakat khususnya siswa dalam meningkatkan keterampilan belajar sebagai modal untuk masa mendatang. Perlunya siswa menghadapi tantangan era society 5.0 ini, maka siswa harus menerapkan pembelajaran berbasis HOTS (higher order thinking skills), yang merupakan proses berfikir siswa dengan level kognitif yang lebih tinggi yang dikembangkan dari berbagai konsep taksonomi pembelajaran. Tujuan dari siswa menerapkan HOTS, yaitu agar meningkatkan kemampuan siswa dalam berfikir kritis pada level yang lebih tinggi. Jenis penelitian ini yaitu penelitian kualitatif dengan metode studi literatur. Hasil dari penelitian ini menerapkan pembelajaran berbasis HOTS di SD kelas tinggi melatih kemampuan siswa untuk berpikir kritis, kreatif, memecahkan masalah sendiri dengan pengetahuan yang dimiliki. Keywords: HOTS, IPA, Era Society 5.0